E-Portofolio Sebagai Evaluasi Penilaian Berkelanjutan Berbasis Kompetensi Dalam Kurikulum Pendidikan Kebidanan: Literatur Review - Mardianah, Lia; Susanti, Ari Indra (Jayapangus Press, 2025)
The development of digital technology and the demands of competency-based education require innovation in assessment systems, particularly in midwifery education. One approach that is increasingly being used is the e-portfolio, which is considered capable of continuously documenting students’ competency achievements. However, there is still a lack of studies that specifically examine the effectiveness of e-portfolios in comprehensively and continuously assessing the competency achievement of midwifery students. This study aims to review the use of e-portfolios as a tool for continuous competency-based assessment in the midwifery education curriculum. This study employs a literature review approach guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The process of literature search and selection was conducted systematically through academic journal databases, research reports, and relevant articles. The study explores the use of portfolios as an assessment tool, the integration of e-portfolios as part of continuous competency-based assessment, and the evaluation of e-portfolio assessment items in the context of midwifery education. The findings indicate that e-portfolios can enhance student engagement in the learning process, allow for more comprehensive and personalized assessments, and facilitate the continuous development of clinical competencies. The conclusion of this study suggests that e-portfolios hold significant potential as a tool for continuous competency-based assessment in the midwifery education curriculum, provided that adequate infrastructure and appropriate training are available. Recommendations are made for further research and the implementation of best practices in the use of e-portfolios in midwifery education.